O dizer e o poder dizer: a assunção da autoria na escola - Silva, Palloma Rios da (2016)
The authorship is one of the roles taken by the subject in the discursive activity. However, it is also, paradoxically, in this function, that lies the annulment of the subject, its dispersion. Under the influence of French Discourse Analysis (DA), more specifically guided by Pêcheux’s (1999; 2009), Orlandi’s (1996; 2012; 2013), Pacífico’s (2012) and Indursky’s (1999) studies, the current research aims to analyze the development of the student’s authorship in the school environment. Here, the authorship was discussed under three perspectives: 1) its relationship with the text; 2) its relationship with the polissemic reading; 3) its relationship with the interdict of the speech. Assuming the hypothesis that the school does not offer proper conditions for the student to develop the “subject-author’s” position, for the school is immersed in the Ideological Formation (IF), in which understands the Language as impeccable, not susceptible to mistakes, different understandings and that the Text is an immutable thing. Bound to verify the effects of the senses in the teacher’s discourse regarding the student’s (non) authorship, meaning that the teacher’s discourse, when immersed in the dominant IF, may interdict on the student’s authorship. It was analyzed three materialities: the discourse of two participating teachers and the 4th and 5th grades student’s oral and written productions in two textual production classes. The activity proposed in said classes was to create a narrative text for one speechless comic strip. The same comic strip was given to both teachers so they could plan their classes. Evidences of attempts of interdict were verified and analyzed in the discourse of both teachers, even if one of them adopted a discourse that could give more chances to the senses’ polysemy in the orality, such as: concernment about the formal aspect of the text, requesting the students to perform a superficial description of the images in the comic strip and not the preset objective to do a narrative text production. Based on the retrieved data it is safe to assume that the students did not fully develop authorship, because: 1) The polissemic reading concept was not motivated; 2) The Text was not seen as heterogeneous, crossed by many discourses; 3) There were attempts of interdict in the teachers’ discourse. To the DA, the text is crossed by many discourses and produces various senses’ effects that vary accordingly to the reader and in what production conditions this reading process happens. When the text is seen as an immutable thing, as if there was a preset sense, the polissemic reading does not occur. The polissemic reading gives condition so the student can produce interpretation gestures, mobilizes the memory and may as well feel responsible for “his own” discourse. It is pertinent to conclude, therefore, that the student’s authorship was silenced.